Impact of Best HRM Practices on Retaining the Best Employees: A Study on Selected Bangladeshi Firms - Hosain, Md. Sajjad (Asian Journal of Social Sciences and Management Studies, 2016)
This study has been developed to endeavor the relationship between ten Human Resource Practices (job analysis, recruitment & selection, adequate training facilities, performance appraisal, adequacy of information, supervisory treatment, opportunities for career development, compensation & benefit, managerial relationship with employees and degree of employee participation in decision making) and their possible impact on employee retention. The research was carried out with a sample size of 252 non-managers and 62 top level managers of 23 public and private corporate firms in Bangladesh. Data have been collected through a detailed structured questionnaire from the respondents. Judgment sampling method has been used to recruit the respondents. Result after careful statistical analysis has drawn a very interesting and unusual conclusion. It has indicated that there is a positive but insignificant relationship between job analysis, adequacy of information, management-employee relationship and participation in decision making with employee retention. The other six independent variables, recruitment & selection, job training facilities, performance appraisal, supervisory treatment, career development and compensation & benefit have negative relationship with employee retention. Among them, job training, compensation & benefit and supervisory treatment have strong negative relationship with employee retention.